Emotional Empathy as a Mechanism of Synchronisation in Child-Robot Interaction - Giannopulu, Irini; Terada, Kazunori; Watanabe, Tomio (Frontiers in Psychology, 2018)
Simulating emotional experience, emotional empathy is the fundamental ingredient of interpersonal communication. In the speaker-listener scenario, the speaker is always a child, the listener is a human or a toy robot. Two groups of neurotypical children aged 6 years on average composed the population: one Japanese (n = 20) and one French (n = 20). Revealing potential similarities in communicative exchanges in both groups when in contact with a human or a toy robot, the results might signify that emotional empathy requires the implication of an automatic identification. In this sense, emotional empathy might be considered a broad idiosyncrasy, a kind of synchronisation, offering the mind a peculiar form of communication. Our findings seem to be consistent with the assumption that children’s brains would be constructed to simulate the feelings of others in order to ensure interpersonal synchronisation.